Optimalisasi Peran Guru Penggerak dalam Pendidikan Merdeka Belajar di SMP Negeri 2 Jikumerasa: Optimalisasi Peran Guru Penggerak Dalam Pendidikan Merdeka Belajar di SMP Negeri 2 Jikumerasa - Hentihu, Vivi Rahim; Badu, Tri Kurnia; Mukadar, Suraya; Loilatu, Siti Hajar; Syafa Lisaholit (LP. Ma'arif Janggan Magetan, 2022)
This study aims to find out: 1. Optimizing the role of movement teacher at SMP Negeri 2 Jikumerasa; 2. What factors that support and hinder the role of movement teacher at SMP Negeri 2 Jikumerasa. This research method is to use descriptive types and approaches of qualitative research. The results of this study show that SMP Negeri 2 Jikumerasa has implemented programs related to movement teacher in independent learning education. the program has been implemented Even though the program was not entirely maximum. The cause of the not being optimal here is that the understanding of the teachers of SMP Negeri 2 Jikumerasa is not optimally related to the role of this movement teacher, so initially Some of the teachers of SMP Negeri 2 jikumerasa do not want to be led and directed by movement teacher, they are indifferent to what the movement teacher does, even though the capacity of a movement teacher is as a learning leader in this case the movement teacher gives an example to other teachers. However, the lack of understanding from these teachers has resulted in some teachers participating and there are some teachers who do not want to follow what is directed by the driving teacher, so the results obtained are not one hundred percent maximum. The factors that support and hinder the role of driving teachers at SMP Negeri 2 Jikumerasa include: 1. The support of the principal; 2. Movement teacher able to position himself as the driving teacher; 3. There is support from fellow teachers; 4. Availability of adequate school facilities and infrastructure.